Enhancement of task oriented maintenance model using secure software desgin maintenence - Abdulrazak, Essa Zaki (2013)
Most of the software today are not secure and contain security vulnerabilities that can be exploited by people with malicious intend to cause financial and physical damage. One of the reasons is that most research efforts have been put into the general development and maintenance processes with the implementation of some models. One such model for maintenance of software is task oriented maintenance model. This maintenance model does not focus on how to maintain secure software. Thus, this project identifies software design issues that need to be addressed in maintenance stage. In order to do this, we enhance the task oriented maintenance model to task oriented security maintenance (TOSiM) model. The proposed enhanced TOSiM model aspired to avoid design vulnerabilities by considering security features. In order to study the concept suitability of the model, two case studies have been conducted with software industry experts and the results are analyzed. The analysis shows that the enhanced model can be used to guide software designers/architects that fulfill their needs for how to maintain secure software design with less vulnerability.